The natural recovery of soil microbial community and nitrogen functions after pasture abandonment in the Amazon region. Issue 9 (25th July 2020) - Pedrinho, Alexandre; Mendes, Lucas William; Merloti, Luis Fernando; Andreote, Fernando Dini; Tsai, Siu Mui
ABSTRACT: We assessed the impacts of forest-to-pasture conversion on the dynamic of soil microbial communities, especially those involved in the N-cycle, and their potential functions, using DNA-metagenomic sequencing coupled with the quantification of marker genes for N-cycling. We also evaluated whether the community's dynamic was reestablished with secondary forest growth. In general, the microbial community structure was influenced by changes in soil chemical properties. Aluminum and nitrate significantly correlated to community structure and with 12 out of 21 microbial phyla. The N-related microbial groups and their potential functions were also affected by land-use change, with pasture being clearly different from primary and secondary forest systems. The microbial community analysis demonstrated that forest-to-pasture conversion increased the abundance of different microbial groups related to nitrogen fixation, including Bacteroidetes, Chloroflexi and Firmicutes. In contrast, after pasture abandonment and with the secondary forest regeneration, there was an increase in the abundance of Proteobacteria taxa and denitrification genes. Our multi-analytical approach indicated that the secondary forest presented some signs of resilience, suggesting that the N-related microbial groups and their potential functions can be recovered over time with implications for future ecological restoration programs. Abstract : The regeneration of secondary forest in the Amazon region indicates that the N-related microbial groups and their functions can be recovered over time.